Information Technology Literacy : Implications on Teaching and Learning - Zoheir Ezziane (Educational Technology & Society, 2007)
This paper aims to discuss the role and impact that information technology (IT) has on the future and existing style of learning and teaching. It highlights the importance of acquiring computer skills and being literate in IT. The focus is put on certain areas related to IT and education which include pedagogy and training to build IT literacy among both educators and learners. Particularly, it covers the current trends in IT development and how it has started to change and will further influence the way learning and teaching will take place in the future. This paper also discusses various theoretical frameworks and methodologies designed to cope with progress in IT. In summary, this paper delivers a message that IT literacy is the key to today’s empowerment and that education is the best foundation for it. Keywords IT literacy, Computer literacy, Teaching and learning, Workforce development
Keywords: apprentissage; compétences; enseignement; lecture numérique; littératie numérique